A serine/threonine protein kinase encoding gene KERNEL NUMBER PER ROW6 regulates maize grain yield - Haitao Jia (Nature Portfolio, 2020)
Selection of kernel number per ear has improved maize yield, but the genetic base is unclear. Here, the authors reveal that a serine/threonine protein kinase KNR6 is a positive regulator of the trait and show in vitro evidences that KNR6 may function through phosphorylating an Arf GTPase-activating protein.